Quality Management Practices in Higher Education Institution: The Case of Institute of Science and Technology - Kamal, Abu Hena Md. Mustafa; Maruf, Saleh Mohammed; Md. Ujjal Hossain (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Although a great number of studies had been done on the concept of quality management in higher education, none had been done within the context of higher education institute that are affiliated under National University in Bangladesh, the case of the Institute of Science and Technology (IST). There was need therefore for a study to be carried out focusing on the IST’s academic services in conjunction with the main QM features. A survey on 36 academic and administrative employees using random sampling were carried out and prepared by SPSS software to find the central tendency and dispersion as well as reliability test was carried out. Collected data were analyzed using Likert Scale (5 point rating scale). From the findings one can conclude that, based on the objectives of the study; Firstly, Institute of Science and Technology has applied quality management to an average extent that is appropriate to its purpose. IST should implement policies and practices to implement quality management to great extent and remove the status quo to be supportive to any formulation of new ideas in order to respond to an ever-changing environment in H.E. Crucially further research should be done to determine how Quality management can contribute to organizational financial performance and customer satisfaction and establish a conceptual model pertinent to the culture and environment of H.E. in Bangladesh.